Administration Management of Hajj Pilgrimage Organization in Increasing Service in the Ministry of Religion Regency of Fifty Cities - Murnika, Yosi; Ridhah, Habibatur; Fadhilah, Savira Maghfiratul (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2025)
This study aims to identify the administrative management of the implementation of the Hajj pilgrimage in improving services, The main problem raised in this article is the lack of knowledge of prospective pilgrims in the process administration in the form of registration, cancellation and payment, administration that is hampered by the network and lack of Human Resources of Hajj officers who master the technical operation of computers in the Ministry of Religion of fifty cities. This study uses a qualitative method in which researchers will trying to find information or data in the field, which is the source of data for this research is Mr. Kasi PHU and PHU employees of the Ministry of Religion in lima puluh cities and districts, as well as 10 Hajj pilgrims. The results of this study shows that the administrative management activities for organizing the Hajj and Umrah pilgrimages Administrative services in office Ministry of Religion regency fifty cities Enough Good because Ministry of Religion lima puluh city try as much as possible Possible For make it easier for prospective pilgrims to respond quickly and understand the processes they go through before leaving until after returning to their homeland, there is no difference between prospective Hajj pilgrims, everything is done the same and as fair as possible, all prospective pilgrims are guided and accompanied starting from the registration process, payment, transfer portion, cancellation, until departure.